Novel Method to Collect Medication Adverse Events in Juvenile Arthritis: Results From the Childhood Arthritis and Rheumatology Research Alliance Enhanced Drug Safety Surveillance Project1. Issue 4 (April 2015) - Ringold, Sarah; Hendrickson, Audrey; Abramson, Leslie; Beukelman, Timothy; Blier, Peter R.; Bohnsack, John; Chalom, Elizabeth C.; Gewanter, Harry L.; Gottlieb, Beth; Hollister, Roger; Hsu, Joyce; Hudgins, Andrea; et al.
Abstract : Objective: Few data are available regarding the rates of serious adverse events (SAEs) and important medical events (IMEs) outside of product‐based registries and clinical trials for juvenile idiopathic arthritis (JIA). The Enhanced Drug Safety Surveillance Project (EDSSP) was developed to pilot a novel system to collect SAEs/IMEs in children with JIA. This analysis reports the results from this 4‐year (2008–2012) EDSSP. Methods: Participating physicians were surveyed monthly to ascertain whether their JIA patients experienced an SAE or IME. Sites were surveyed every 6 months to determine the number of unique JIA patients seen at each site during that 6‐month period. Reporting rates were calculated per 100 person‐years and 95% confidence intervals (95% CIs) were calculated based on a Poisson distribution. Results: Thirty‐seven Childhood Arthritis and Rheumatology Research Alliance sites with 115 physicians participated. The mean response rate to the monthly surveys was 65%. There were 147 total SAEs and 145 total IMEs. The largest proportion of SAEs and IMEs occurred in children with polyarticular JIA (39% and 37%, respectively). The majority of SAEs and IMEs were reported for patients receiving therapy with biologic agents (76% and 69%, respectively). The total event rate for SAEs and IMEs combined was 1.07 events per 100 person‐years (95% CI 0.95–1.19). The rates for SAEs and IMEs were 0.54 per 100 person‐years (95% CI 0.45–0.63) and 0.53 per 100 person‐years (95% CI 0.49–0.62), respectively. Conclusion: The EDSSP provided a simple tool for SAE/IME reporting within an established research network and resulted in a similar range of reported events as captured by a traditional product‐based registry.